Cantilever Steel Industrial Building Located on a Rocky Hill. (2016) - Georgescu, Mircea; Ungureanu, Viorel
Abstract: The object of the paper is an industrial building, part of a vineyard, located in a rocky zone of Arad County Romania. The investor and architect requirements led to locate the building at a height of 14.00 m, partially supported by the rocky wall of the hill at one end, while the other end is supported by a reinforced concrete rectangular tower, built near the hill. The show room area (located into a glazed cantilever zone of the building) spans 10.0 m beyond the support tower. Thus, most of the building spans in the air, creating an impression of "suspension". The paper describes some of the problems confronted by the structural engineer during the design phase, also influenced by architectural concepts.